The Relationship Between Peer Interaction and Student Learning Activeness at The Al-Quran Education Park (TPQ) Baiturahman Sialang Mosque - Amelia, Rose; 'Aini, Wirdatul (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research is based on the low level of student learning activity at TPQ Baiturahman Sialang. This is thought to be influenced by peer interactions. This research aims to: (1) see a picture of student peer interactions at TPQ Baiturahman Sialang; (2) see a picture of students' active learning at TPQ Baiturahman Sialang; (3) looking at the relationship between peer interactions and students' active learning at TPQ Baiturahman Sialang. This research is a type of correlational quantitative research with a population of 30 people with samples using cluster random sampling techniques. This research shows the results, namely: (1) student peer interaction at TPQ Baiturahman is not going well; (2) student learning activities at TPQ Baiturahman are categorized as less active in the learning process; (3) There is a positive and significant relationship between peer interaction and student learning activeness at TPQ Baiturahman Sialang.Keywords: peer interactions, Learning activity, Al-Quran Education Park